The link between computer use and job satisfaction: The mediating role of job tasks and task discretion - Saverio Minardi; Carla Hornberg; Paolo Barbieri; Heike Solga (British Journal of Industrial Relations, 2023)
This study focuses on the consequences of the use of computerized work equipment (hereafter: computer use) on the content and quality of work. It investigates, first, the relationship between computer use and both job tasks and task discretion and, second, their mediating role for the relationship between computer use and job satisfaction. With our German-UK comparison, we contribute to the long-standing debate on the upskilling/de-skilling nature of the use of technology and its repercussions on the quality of work. We analyse data from the Skills and Employment Surveys for the UK and the BIBB/BAuA Employment Surveys for Germany using structural equation modelling. In line with the literature on routine-biased technological change, we show that computers are complementary to the performance of less routine and more abstract cognitive tasks and that this relationship is conducive to a higher level of task discretion and job satisfaction in both countries. Accounting for differences in job tasks performed, we find a negative direct effect of computer use on both task discretion and job satisfaction in the United Kingdom but not in Germany. Our results indicate that the ultimate effect of computer use on both task discretion and job satisfaction depends on the institutional contexts in which technology is introduced.
Keywords: 330